Justice in Employment Law : A Philosophical Study of the Relationship Between Employers and Employees - Andri Herman Setiawan; Firman Nurdiyansyah Sunandar; Ahmad Juaeni; Johannes Triestanto (International Journal of Law, Crime and Justice, 2025)
This study examines justice in employment law from the perspective of legal philosophy, focusing on the relationship between employers and workers in Indonesia. Based on Article 27 paragraph (2) and Article 28D paragraph (2) of the 1945 Constitution, justice in employment relations is considered as one of the manifestations of human rights that must be guaranteed by the state. However, in practice, the imbalance in the bargaining position between employers and workers often creates injustice, especially in wages, job protection, and the fulfillment of basic workers' rights. Through a legal philosophy approach, this study analyzes the application of the concepts of distributive, commutative, and retributive justice in employment relations. The results of the study show that although employment regulations, such as Law Number 13 of 2003 concerning Employment, have attempted to create justice, their implementation still faces various obstacles, including weak supervision and bias towards economic interests. This study has theoretical benefits in deepening the study of legal philosophy related to justice in industrial relations, as well as practical benefits in providing recommendations for policy makers to improve employment regulations. Thus, this research is expected to be a foundation for creating fairer and more balanced working relationships in Indonesia.